Environmental magnetic and petroleum hydrocarbons records in sediment cores from the north east coast of Tamilnadu, Bay of Bengal, India - Venkatachalapathy, R.; Veerasingam, S.; Basavaiah, N.; Ramkumar, T.; Deenadayalan, K. (My University, 2011)
In this study, mineral magnetic properties and petroleum hydrocarbons were statistically analysed in four sediment cores (C1, A1, T1 and K1) from the north east coast of Tamilnadu, India to examine the feasibility of PHC concentrations assessment using magnetic susceptibility. The C1 and A1 cores reveal a clear horizon of increase in PHC above 35 and 50 cm respectively suggesting the excess anthropogenic loading occurred in the recent past. Magnetic properties which were enhanced in the upper part of the sediment cores were the result of ferrimagnetic minerals from anthropogenic sources. Factor analysis confirmed that the input of magnetic minerals and petroleum hydrocarbons in Chennai coastal sediments are derived from the same sources. The present study shows that instead of expensive and destructive PHC chemical methods, magnetic susceptibility is found to be a suitable, cheap and rapid method for detailed study of petroleum hydrocarbon contamination in marine sediments.
Keywords: Magnetic susceptibility; Remanent magnetization; Petroleum hydrocarbons; Marine pollution; Multivariate analysis